2006
DOI: 10.1681/asn.2005050545
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C and Mortality Risk in the Elderly

Abstract: Kidney dysfunction is known to decrease life expectancy in the elderly. Cystatin C is a novel biomarker of kidney function that may have prognostic utility in older adults. The association of cystatin C with mortality was evaluated in a biracial cohort of black and white ambulatory elderly and compared with that of serum creatinine concentrations. The Health, Aging and Body Composition study is a cohort of well-functioning elderly that was designed to evaluate longitudinal changes in weight, body composition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
125
2
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(144 citation statements)
references
References 27 publications
(15 reference statements)
12
125
2
5
Order By: Relevance
“…This association between inflammatory markers (CRP, interleukin-6 and tumour necrosis factor) and serum cystatin concentrations has been reported in most of the studies which showed a relationship between CysC and cardiovascular disease (218,224,229,233) or in populations at high renal or cardiac risk, such as diabetics (234). Except for the PRIME study (224), however, the association of CysC/cardiovascular event remains when inflammatory markers are included in the multivariate analysis (218,229). Interestingly, the association between inflammatory markers and CysC appeared to be linear in the ''Cardiovascular Health Study'' cohort, whereas it produces a U-shaped curve with creatinine (177).…”
Section: High Cysc Concentrations May Reflect the Existence Of A Low supporting
confidence: 52%
“…This association between inflammatory markers (CRP, interleukin-6 and tumour necrosis factor) and serum cystatin concentrations has been reported in most of the studies which showed a relationship between CysC and cardiovascular disease (218,224,229,233) or in populations at high renal or cardiac risk, such as diabetics (234). Except for the PRIME study (224), however, the association of CysC/cardiovascular event remains when inflammatory markers are included in the multivariate analysis (218,229). Interestingly, the association between inflammatory markers and CysC appeared to be linear in the ''Cardiovascular Health Study'' cohort, whereas it produces a U-shaped curve with creatinine (177).…”
Section: High Cysc Concentrations May Reflect the Existence Of A Low supporting
confidence: 52%
“…Several studies have suggested that the prevalence of arterial stiffness may be higher in black than in white individuals, possibly because the severity of hypertension and diabetes is worse in black individuals. 25,26 Similarly, studies in both CKD and non-CKD have reported higher PWV in those with diabetes in comparison with those without diabetes. 27,28 Finally, one could hypothesize that prevalent CHD may modify the relationship between kidney function and aPWV.…”
Section: Discussionmentioning
confidence: 98%
“…Because the splines did suggest a possible nonlinear association of cystatin and PWV, especially in those with cystatin C Ն2.0 mg/L, we also modeled cystatin C as a categorical variable represented as low (Ͻ0.84 mg/L), medium (0.84 to 1.18 mg/L), and high (Ն1.19 mg/L) on the basis of our previous work. 25 In the case of eGFR Ͻ60 ml/min per 1.73 m 2 , the percentage increase in aPWV corresponds to a percentage change from the reference eGFR category of Ͼ60 ml/min per 1.73 m 2 . Because race, diabetes, and CHD could modify the relationship between cystatin C and aPWV, we evaluated interactions with these covariates and conducted stratified analyses within subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest that eGFR by cystatin C (eGFR cystatin ) has a stronger association with mortality and cardiovascular disease than does eGFR creatinine (4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%